2017
DOI: 10.1042/etls20160015
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins: antibiotics in the age of the microbiome

Abstract: Antibiotics have revolutionised the treatment of infectious disease and improved the lives of billions of people worldwide over many decades. With the rise in antimicrobial resistance (AMR) and corresponding lack of antibiotic development, we find ourselves in dire need of alternative treatments. Bacteriocins are a class of bacterially produced, ribosomally synthesised, antimicrobial peptides that may be narrow or broad in their spectra of activity. Animal models have demonstrated the safety and efficacy of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 84 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…They may also directly inhibit pathogens. Finally, bacteriocins may act as signaling peptides, either signaling other bacteria through quorum sensing or signaling cells of the host immune system and hence modulating host immune system (Egan, Ross and Hill 2017 ). In a study by Pablo et al .…”
Section: Evaluation Of Bacteriocin Safetymentioning
confidence: 99%
“…They may also directly inhibit pathogens. Finally, bacteriocins may act as signaling peptides, either signaling other bacteria through quorum sensing or signaling cells of the host immune system and hence modulating host immune system (Egan, Ross and Hill 2017 ). In a study by Pablo et al .…”
Section: Evaluation Of Bacteriocin Safetymentioning
confidence: 99%
“…More detailed information about the structure, characteristics, properties, and modes of actions of each class of bacteriocins produced by Gram-positive bacteria, in particular produced by CoNS, are comprehensively and recently reviewed elsewhere [408,409]. Although initially thought to only target closely related bacteria, some bacteriocins have a broader spectrum of activity affecting bacteria across different genera [410] or even transphylum [407]. Besides presenting a variable spectrum of activity, their high diversity [411], high stability at elevated temperatures and wide range of pH [412,413], relatively low cytotoxicity [407,414], and amenability to bioengineering [410] render bacteriocins interesting for an array of applications in food, agriculture, veterinary, cosmetics, and pharmaceutical industries (reviewed in [415][416][417]).…”
Section: Bacteriocinsmentioning
confidence: 99%
“…Studies have revealed that nisin and other structurally related lantibiotics use the membrane-bound peptidoglycan precursor lipid II as a docking molecule, which consequently promotes two bactericidal activities, pore formation and inhibition of peptidoglycan biosynthesis (25). Significantly, lantibiotics have been shown to possess activity against antibiotic-resistant targets such as vancomycin-resistant enterococci (VRE) and methicillin-resistant Staphylococcus aureus (MRSA) and may have the potential to mitigate the looming global AR crisis (26).…”
mentioning
confidence: 99%